Problems subsidies in the sphere of agriculture - Iskendirova, S.K.; Konuspayev, R.K.; Demesinov , T.Zh. (BUKETOV BUSINESS REVIEW, 2019)
The trends of budget subsidies in the sphere of agriculture of the Republic of Kazakhstan are studied, the situation with significant changes in the system of subsidizing the agro-industrial complex from the national budget in the period from 2012 to 2018 is analyzed. The directions of subsidizing in the following areas: reimbursement of expenses incurred by the subject of agriculture in investment; subsidizing the interest rate on credit and leasing obligations in the direction of financial recovery of agribusiness entities; subsidizing interest rates for lending and leasing for the purchase of farm animals, machinery and technological equipment; subsidizing procurement organizations in the agricultural sector of the amount of value added tax paid to the budget within the accrued value added tax. Due to the fact that subsidies are provided in order to increase the availability of certain types of resources, it was stated that the economic importance of subsidies is to increase the competitiveness of enterprises (industry), which are targeted subsidies. In the process of subsidizing, the following shortcomings were identified: the rules of investment subsidies do not take into account the criteria depending on the potential of regional development; the rules of subsidizing do not regulate the maximum amount of funding for directions, thus there is a risk of lack of funds for directions from the lower number of priorities; lending for the purchase of farm animals, machinery and technological equipment subsidizing interest rates in most cases is not in demand in the regions. Planning of funds is carried out in order to reserve annually allocated volumes and their further redistribution. Taking into account that the subsidizing of interest rates in obtaining leasing intersects with the investment subsidy (incentive plan), and the application of state support measures (subsidizing the interest rate on loans and leasing of technological equipment, for the purchase of farm animals, as well as leasing of agricultural machinery with the provision of investment subsidies) is provided by law, the process of assessing the effectiveness of subsidies and their impact on the industry is becoming more complicated.Replenishment of working capital means stimulating short-term lending and does not contribute to the increase and expansion of production.